2012
DOI: 10.3758/s13415-012-0116-8
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to (non)valent task disturbance

Abstract: The cognitive system adapts to disturbances caused by task-irrelevant information. For example, interference due to irrelevant spatial stimulation (e.g., the spatial Simon effect) typically diminishes right after a spatially incongruent event. These adaptation effects reflect processes that help to overcome the impact of task-irrelevant information. Interference with (or interruption of) task processing can also result from valent (i.e., positive or negative) stimuli, such as in the "affective Simon" task. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 51 publications
(84 reference statements)
0
15
1
Order By: Relevance
“…Here, the adaptation-by-binding model would predict generalizable benefits of conflict-enhanced binding of attention to (especially task-relevant) stimulus features, regardless of which type of conflict elicited the putative arousal response and binding process; this runs counter to empirical findings, however, because even with identical task-relevant features (e.g., ink color), conflict-general CSEs are not observed in such studies (Wendt et al, 2006; Egner et al, 2007; Boy et al, 2010; Akcay and Hazeltine, 2011; Schlaghecken et al, 2011; Kim et al, 2012; Kunde et al, 2012). There are some studies showing CSEs to selectively cross “conflict boundaries” when task-relevant features are shared rather than distinct (e.g., Notebaert and Verguts, 2008), but in these studies, changes between conflict types also represent switches between tasks, such that they cannot directly speak to the conflict-specificity (or lack thereof) of CSEs (see Egner, 2008).…”
Section: A Multi-level Learning Perspective On the Modulation Of Congmentioning
confidence: 70%
See 1 more Smart Citation
“…Here, the adaptation-by-binding model would predict generalizable benefits of conflict-enhanced binding of attention to (especially task-relevant) stimulus features, regardless of which type of conflict elicited the putative arousal response and binding process; this runs counter to empirical findings, however, because even with identical task-relevant features (e.g., ink color), conflict-general CSEs are not observed in such studies (Wendt et al, 2006; Egner et al, 2007; Boy et al, 2010; Akcay and Hazeltine, 2011; Schlaghecken et al, 2011; Kim et al, 2012; Kunde et al, 2012). There are some studies showing CSEs to selectively cross “conflict boundaries” when task-relevant features are shared rather than distinct (e.g., Notebaert and Verguts, 2008), but in these studies, changes between conflict types also represent switches between tasks, such that they cannot directly speak to the conflict-specificity (or lack thereof) of CSEs (see Egner, 2008).…”
Section: A Multi-level Learning Perspective On the Modulation Of Congmentioning
confidence: 70%
“…First, we can likely reject the notion of a very general effect, whereby exposure to an incongruent trial would lead to broad performance benefits regardless of the specifics of the task-demands on the forthcoming trial. This rejection is based on a large number of studies that have documented the CSE to be domain- or conflict-specific (e.g., Wendt et al, 2006; Egner et al, 2007; Boy et al, 2010; Funes et al, 2010; Akcay and Hazeltine, 2011; Schlaghecken et al, 2011; Kim et al, 2012; Kunde et al, 2012; for reviews, see Egner, 2008; Braem et al, 2014). Such conflict-specificity is most appropriately assessed in protocols that combine factorially two distinct types of conflict into a single task, such that the independence of conflicts (i.e., additive main effects) and their potential sequential (in)-dependence can be assessed simultaneously, and in the absence of potential task-switching effects when alternating between conflicts in a non-factorial design (for an extended discussion, see Egner, 2008).…”
Section: A Multi-level Learning Perspective On the Modulation Of Congmentioning
confidence: 99%
“…Following its initial report in the context of an Eriksen flanker task (Gratton et al, 1992), it was replicated in a wide variety of tasks, including the color–word (e.g., Kerns et al, 2004), numerical (e.g., Cohen Kadosh et al, 2011), and gender face-word Stroop (e.g., Egner et al, 2008), the social (e.g., Kunde et al, 2012) and spatial Simon (e.g., Stürmer et al, 2002), the parity judgment (e.g., the spatial–numerical association of response codes or SNARC effect; Pfister et al, 2013), the picture–word interference (e.g., Duthoo et al, in revision), the perceptual fluency (e.g., Dreisbach and Fischer, 2011), the prime-target (e.g., Kunde and Wühr, 2006), and affective priming task (e.g., Frings and Wentura, 2008). Also in studies on arithmetics, difficulty arising from inappropriate strategy execution is susceptible to sequential, trial-to-trial performance adjustments (e.g., Uittenhove and Lemaire, 2012; Lemaire and Hinault, 2013).…”
Section: Conflict Adaptationmentioning
confidence: 99%
“…Still, this experimental strategy is somewhat problematic: by excluding more and more trial transitions, the decision on the presence or absence of a CSE is made on an increasingly small and thus special subset of the data. In an attempt to circumvent this problem, Notebaert and Verguts (2007) proposed a multiple regression approach to statistically separate the influence of bottom-up feature repetitions and top-down control (see also Braem et al, 2012; Kunde et al, 2012). Another solution is to preclude trial transitions that are contaminated with feature integration a priori .…”
Section: Feature Integrationmentioning
confidence: 99%
“…Kim et al ( 2012 ) also found conflict type specific CSEs when using a factorial combination of an arrow and color Stroop task. Last, Kunde et al ( 2012 ) extended this research into the affective domain, by factorially combining a Simon task and an affective interference task. The affective interference task either consisted of a conflict between the relevant and irrelevant stimulus dimension (i.e., affective pictures and affective words, Experiment 1), or a conflict between the relevant response and irrelevant stimulus dimension (i.e., affective verbal responses and smiley faces, Experiment 2).…”
Section: Transfer Of the Congruency Sequence Effectmentioning
confidence: 99%